Let the Little Children Come: Child Rearing as Challenge to Contemporary Christian Ethics - Wall, John (Horizons, 2004)
A contemporary culture of market individualism in the United States today is increasingly marginalizing the lives of children. This situation requires Christian ethicists to raise once again, as in the historical past, the question of the larger meaning and purpose of child rearing as a serious disciplinary concern. This paper identifies fundamental issues of child rearing ontology, teleology, deontology, and practice, and maps out some newly emerging Christian ethical responses by communitarians, liberationists, and covenantalists. It then develops a larger social ethics of child rearing—drawing on a range of historical theological resources—able to speak to children's issues in a disciplinarily complex, publicly meaningful, and culturally transformative way. Its argument is that child rearing should be rescued from its increasing social privatization through a revised covenantal social ethic that strengthens the unique tasks of families but also places them within a larger interdependent nexus of community and state supports.